A comparative study of nanovoid growth in FCC metals. Issue 32 (12th November 2017) - Ponga, M.; Ortiz, M.; Ariza, M. P.
Abstract: Previous HotQC studies of Cu nanovoids undergoing volumetric expansion conducted by the authors have uncovered a quasistatic-to-dynamic transition at a critical strain rate of the order of . At low strain rates nanovoid expansion takes place under essentially isothermal conditions, whereas at high strain rates it happens under essential adiabatic conditions. In this paper, we present a comparative study concerned with two different scenarios, each representing a variation on the reference case presented in [1]: (i) aluminium (Al) nanovoids undergoing volumetric expansion; and (ii) copper (Cu) nanovoids undergoing uniaxial deformation. Scenario (i) addresses material specificity by replacing Cu by Al in the reference case, whereas scenario (ii) addresses the effect of triaxiality by replacing volumetric expansion by uniaxial expansion in the reference case. We find a distinct quasistatic-to-dynamic transition in both scenarios, which suggests that the transition is indeed universal, i.e. material and strain-triaxiality independent. By contrast, the fine structure of the dislocation mechanisms that mediate void growth are strongly material and loading specific.